(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article highlights some results of scientific and practical research carried out on the modernization of architectural and landscape, artistic and technical visualization of territories along the Tashkent-Samarkand railway, which is one of the important international tourist routes of Uzbekistan.